PENGARUH LIMBAH CAIR PABRIK KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao) - Rinaldi .; Hanibal .; Wira Syahputra (Bioplantae, 2012)
This research aim is  to evaluate the effect of Palm oil liquid waste  to the cacao seedling growth. This research was conducted at Faculty of Agriculture Research Farm. This research was arrangement with Completely Randomized Block Design (CRBD) consisting of  six treatment of dosage with  four replications, so there are 24  polybag. The treatment are  dosage 0.0 Lpolybag -1 , 0.4 Lpolybag -1,0.8 Lpolybag -1, 1.2 Lpolybag -1, 1.6 Lpolybag -1 dan 2.0 Lpolybag -1. The Results showed  that there were significantly effects of dosage to all growth parameter, such as cacao seedling height, diameter of branch, total leaf area, root dry weight and plant dry weight. Dosages 1.6 L polybag-1, was the best effect on all growth parameters.